(untitled) (ARQUISUR Revista, 2020)
The enforcement in the Chilean territory of the law 20,958 of Contribution to Public Space will cause a significant change in the city. Impacts on the city planning and territorial administrations instruments, the productive sector and the its community. It seems advisable and necessary make visible in advance the effects in order that the public policy acceptance, construction and consolidation would be consistent and adequate, allowing to overcome the scarcity of endowments and opportunities for urban life. Situation generated in time as a result of the urban densification processes that increased the occupation and diversified the applications.The analysis of the evolution and modes of production of residential buildings in height in Santiago city allowed to validate the relevance of the construction of public space that solves the functional requirements, promotes integration, consolidates community life and minimizes the effect density by compensating the agglomeration with amenities for recreation, showing that independent of the political, economic, social and cultural changes that occur on society, the social welfare caused by the satisfaction of collective needs is achieved with access to goods and services available to society as a whole.